PEMANFAATAN MEDIA DIGITAL DALAM PENGEMBANGAN DESA WISATA DI DESA BURAI KABUPATEN OGAN ILIR SUMATERA SELATAN - Huspita sari, Feni (Lentera Jurnal Manajemen, 2024)
Burai Village, which is located in Ogan Ilir Regency, South Sumatra Province, with an area of around 2.66 square kilometers, is one of the tourism villages that is starting to be developed by the Ogan Ilir Regency government. In an increasingly advanced era, digital media cannot be separated from almost all community activities, one of which is developing tourism in Burai village. This article explains the Community Service activities of the Annisa Dwi Salfaritzi College of Administration and Government Palembang in Burai Village with the theme "Utilization of digital media in developing tourist villages in Burai Village, Ogan Ilir Regency, South Sumatra." The method used is an initial survey to provide an understanding of the importance of using digital media in developing the potential of tourist villages so that the community can participate in promoting and empowering community abilities through digital media more effectively. Key word : Tourism Village, Digital Media, Community Service